Candidates for antimalarial compounds in secondary metabolites of Streptomyces sp. InaCC 1497 and AB8 - Endah Setyaningrum; Jihan Fikra Angelia; Kusuma Handayani; Achmad Arifiyanto; Dzul Fithria Mumtazah (Biogenesis: Jurnal Ilmiah Biologi, 2023)
One effort to reduce the transmission of malaria is the provision of antimalarial drugs. However, the use of drugs that are not according to standards causes resistance to Plasmodium. This condition triggers the exploration of various natural compounds to prevent malaria. Secondary metabolites derived from Streptomyces sp. are known to have antimalarial activity. However, information related to secondary metabolites from Streptomyces sp. strains InaCC A497 and AB8 as antimalarials are not yet known. The purpose of this study was to determine the metabolite compounds secondary contained in Streptomyces sp. strains InaCC A497 and AB8 as antimalarial candidates. This research method is descriptive by testing secondary metabolites which are carried out through chemical compound tests, thin layer chromatography (TLC), fourier transform infra-red (FT-IR), and gas chromatography-mass spectroscopy (GC-MS). Test results of chemical compounds and FT-IR analysis of Streptomyces sp. InaCC A497 contains alkaloids, flavonoids, and triterpenoids, while Streptomyces sp. AB8 contains alkaloids and tannins. In the TLC test, Streptomyces sp. InaCC A497 produced an Rf value of 0.257 and Streptomyces sp. AB8 of 0.314. Based on the GC-MS test, Streptomyces sp. InaCC A497 produces acetic acid compounds, ethyl ester including the ester group, and 1,2-benzene dicarboxylic acid, dioctyl ester including the alkaloid group. Streptomyces sp. AB8 produces the compound 2-pentadecyn-1-ol which belongs to the aromatic alcohol group and cochlioquinone A belongs to the quinone group. Both compounds have antimalarial activity.